2012
DOI: 10.1021/es302017e
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Environmental Fate of β-HCH in Asian Soil and Association with Environmental Factors

Abstract: Chinese Gridded Pesticide Emission and Residue Model was applied to simulate long-term environmental fate of β-HCH in Asia spanning 1948−2009. The model captured well the spatiotemporal variation of β-HCH soil concentrations across the model domain. β-HCH use in different areas within the model domain was simulated respectively to assess the influence of the different sources of β-HCH on its environment fate. A mass center of soil residue (MCSR) was introduced and used to explore environmental factors contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…Modeling results suggested that contamination of β-HCH in soil residue of the TP is due to Indian, Southeast Asian and Chinese sources, driven by the Indian summer monsoon and East Asian monsoon respectively. Further, they found that residue levels β-HCH from Indian sources was higher than from South Asian countries (Xu et al, 2012). Likewise, Xu et al (2013a) found a significant influence of India γ-HCH emissions on western China, assisted by the Indian monsoon, leading to a north-eastward migration of contaminants from India.…”
Section: The Role Of India In the Global Distribution Of Persistent Omentioning
confidence: 98%
See 1 more Smart Citation
“…Modeling results suggested that contamination of β-HCH in soil residue of the TP is due to Indian, Southeast Asian and Chinese sources, driven by the Indian summer monsoon and East Asian monsoon respectively. Further, they found that residue levels β-HCH from Indian sources was higher than from South Asian countries (Xu et al, 2012). Likewise, Xu et al (2013a) found a significant influence of India γ-HCH emissions on western China, assisted by the Indian monsoon, leading to a north-eastward migration of contaminants from India.…”
Section: The Role Of India In the Global Distribution Of Persistent Omentioning
confidence: 98%
“…The distribution pattern throughout the TP strongly suggests that the main sources of OCPs may be from the Indian subcontinent. Xu et al (2012) assessed the environmental fate and source-receptor relationships of β-HCH from 1948 to 2009 over Asia, and its association with environmental factors using ChnGPERM. Modeling results suggested that contamination of β-HCH in soil residue of the TP is due to Indian, Southeast Asian and Chinese sources, driven by the Indian summer monsoon and East Asian monsoon respectively.…”
Section: The Role Of India In the Global Distribution Of Persistent Omentioning
confidence: 99%
“…9−11 Despite primary emissions of OCPs being restricted or banned completely in most parts of the world, large burdens are currently stored in agricultural soils, especially in areas where they were widely used in the past. 12,13 This is the case in China, where OCPs were used in agriculture until 1983. 14 A global ban resulted in a general and significant decline in atmospheric concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Indian monsoon provides a route of favorable atmospheric transport from India to China in spring and summer. 13 Higher atmospheric concentration levels of many POPs in India 14−17 than in China 18 would yield significant deposition of these contaminants to Chinese environment through LRAT. 19 γ-Hexachlorocyclohexane (HCH), listed as a new POP by the Stockholm Convention in 2009, is one of the toxic chemicals extensively used in India 14−17 and China.…”
Section: Introductionmentioning
confidence: 99%